2015
DOI: 10.1165/rcmb.2014-0297rt
|View full text |Cite
|
Sign up to set email alerts
|

Bactericidal/Permeability-Increasing Protein Fold–Containing Family Member A1 in Airway Host Protection and Respiratory Disease

Abstract: Bactericidal/permeability-increasing protein fold-containing family member A1 (BPIFA1), formerly known as SPLUNC1, is one of the most abundant proteins in respiratory secretions and has been identified with increasing frequency in studies of pulmonary disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
54
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(58 citation statements)
references
References 86 publications
(193 reference statements)
1
54
0
3
Order By: Relevance
“…BPIFB1 expression is increased in advanced cystic fibrosis (8) and it is also robustly expressed in the bronchiolized epithelium lining the honeycomb cysts in usual interstitial pneumonia (2). BPIFA1 is the best characterized member of the PLUNC family and previous studies have identified multiple protective roles against respiratory infections and inflammation (9). Data on the function of BPIFB1 are much more limited but it has been hypothesized to also function in the innate defense of the airways.…”
mentioning
confidence: 99%
“…BPIFB1 expression is increased in advanced cystic fibrosis (8) and it is also robustly expressed in the bronchiolized epithelium lining the honeycomb cysts in usual interstitial pneumonia (2). BPIFA1 is the best characterized member of the PLUNC family and previous studies have identified multiple protective roles against respiratory infections and inflammation (9). Data on the function of BPIFB1 are much more limited but it has been hypothesized to also function in the innate defense of the airways.…”
mentioning
confidence: 99%
“…RNA gene expression profiling of CLCA1-CM-versus pcDNA-CM-stimulated WT alveolar macrophages was performed via microarray analysis and identified other genes regulated by CLCA1 which play a role in early immune responsesGene nameDescriptionlog FCBiological relevance Ccl5 Chemokine (C-C motif) ligand 5 (Ccl5)− 2.71Plays an active role in leukocyte recruitment to sites of inflammation, including T cells, macrophages, eosinophils, and basophils (Aldinucci and Colombatti 2014) Emr4 EGF-like module containing, mucin-like, hormone receptor-like sequence 4 (Emr4)− 2.26Predominantly expressed on resident macrophages, expression is up-regulated following macrophage activation (Stacey et al 2002) Bpifa1 BPI fold containing family A, member 1 (Bpifa1)2.18Abundantly secreted in the respiratory tract, antimicrobial- and anti-biofilm properties, regulates mucociliary clearance and downstream chemokine CCL24 (eotaxin-2) expression (Britto and Cohn 2015) Ccr7 Chemokine (C-C motif) receptor 7 (Ccr7)− 2.15Expressed in lymphoid tissues, activates B and T lymphocytes, controls the migration of memory T cells to inflamed tissues (NCBI—C–C motif chemokine receptor 7 2016), regulates T cell trafficking and compartmentalization within secondary lymphoid organs (Sharma et al 2015) Il-1β Interleukin 1 beta (Il-1β)− 2.13Produced by activated macrophages, mediator of the inflammatory response (NCBI—Interleukin-1 beta 2016a), involved in cell proliferation, differentiation, and apoptosis (NCBI—Interleukin-1 beta 2016b) Aoah Acyloxyacyl hydrolase (Aoah)− 2.13Enzyme that catalyzes the hydrolysis of acyl chains from bacterial LPS, modulates host inflammatory response to Gram-negative bacteria (NCBI—acyloxyacyl hydrolase 2016) Ly6i Lymphocyte antigen 6 complex, locus I (Ly6i)− 2.12Takes part in differentiation of various hematopoietic lineages, highly present on immature granulocytes and monocytes, could function in a common pathway for T and B lymphocyte development, useful in characterizing different stages of T lymphocyte development and activation (Pflugh et al 2000) Ly6c1 Lymphocyte antigen 6 complex, locus C1 (Ly6c1)− 2.12…”
Section: Resultsmentioning
confidence: 99%
“…Захворювання респіраторного тракту певною мірою пов'язані з біологічними властивостями бак-терицидного білка, що збільшує проникність (BPI) [12]. Цей білок міститься в азурофільних гранулах нейтрофілів людини, зв'язується з ліпідом A та про-являє бактерицидну дію щодо багатьох грамнега-тивних бактерій.…”
unclassified
“…Завдяки високій афінності BPI до ліпідів А ліпополісахаридів антимікробна активність даного білка у фізіологічних наномолярних концентраціях більшою мірою виражена відносно грамнегативних бактерій. Завдяки своїм антибактеріальним влас-тивостям BPI обмежують бактеріальний ріст, по-слаблюють формування бактеріальних біоплівок і посилюють опсонізацію бактерій [12]. Захисна дія BPI відносно L-форм грампозитивних бактерій, грибів і Toxoplasma gondii проявляється лише за на-явності високих концентрацій даного пептиду [6].…”
unclassified
See 1 more Smart Citation